Hidden Economies and the Socially Optimal Fiscal-Tax to Liquidity-Tax Ratio - Marco G. Ercolani (Economics: The Open-Access, Open-Assessment E-Journal, 2007)
Differential tax analysis is used to show how the socially optimal fiscal-tax to liquidity-tax ratio changes with the relative size of the tax-evading hidden economy. The smaller the relative size of the hidden economy, the larger the optimal fiscal-tax to liquidity-tax ratio. The empirical cross-section and panel evidence supports this theoretical result.
Keywords: O17; H21; E52; E31; 330; inflation tax; hidden/shadow/underground economy; seigniorage; Schattenwirtschaft; Inflationssteuer; Steuervermeidung; Münzgewinn; Optimale Besteuerung